The performance of monetary policy : a comparison between civil-law and common-law countries - Zakaria, Zukarnain (Faculty of Management and Human Resource Developemant, 2007)

(untitled)
The objective of this paper is to compare the effectiveness of monetary policy between civillaw countries and common-law countries by investigating the impulse response of monetary policy actions on the level of output. This is to determine whether countries of common-law origin are less sensitive to monetary policy actions compared with civil-law countries. Theoretically, we expected that monetary policy is more effective in civil-law countries where their financial structures are more bank-based as compared to common-law countries where their financial structures are more market-based. The impulse response functions were generated through the estimation of first-differences VAR consisting of five variables. The findings show the impact of monetary policy is relatively stronger, responds more quickly and long lasting in civil-law countries compared with common-law countries.